Development of a Multimedia-Based Virtual Tour Learning Media: Sociology Subjects - Saif, Fakhruna; Tanjung, Samsidar; Panjaitan, Keysar (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to develop multimedia-based learning media through virtual tours in sociology subjects at SMA Negeri 1 Binjai, Langkat. The background of this research is based on technological developments in the industrial era 4.0, which requires education to adapt to these advances, especially for the Alpha generation, who are very familiar with technology. Interesting and effective learning media are very necessary to increase student interest and learning outcomes. The research method used is research and development (R&D) with the Borg & Gall model, which consists of several stages, starting from initial research to field trials. The research results show that virtual tour learning media is effective in increasing student engagement and learning outcomes. The use of this medium makes it easier to access information, increases the attractiveness of learning material, and allows students to learn independently and interactively. This research was carried out at SMA Negeri 1 Binjai, Langkat, in class X of SMA in the 2023–2024 even-semester academic year. The research results show that: (1) multimedia-based virtual tour learning media is suitable for use in sociology subjects at SMA Negeri 1 Binjai, Langkat; (2) multimedia-based virtual tour learning media is more effectively used in sociology subjects at SMA Negeri 1 Binjai, Langkat when compared to PowerPoint media.